Implementation and impact of mobile health (mHealth) in the management of diabetes mellitus in Africa: a systematic review protocol - Jean Claude Mutabazi; Ezekiel Musa; Franklin Okechukwu Dike; Blessing Chinenye Ubani; Ahmed Sherif Isa; Chidiebele Ezeude; Henry Iheonye; Isah Idris Ainavi (BMJ Open)
Introduction The WHO has proposed the concept of mobile health (mHealth) to support healthcare systems delivery worldwide. mHealth basically involves the use of Information and Communication Technology for healthcare provision or delivery services. Africa has seen a remarkable increase in mobile phone availability and usage in the last decade. The incidence and prevalence of diabetes mellitus (DM) in Africa have also been on the increase in the last decade, in sharp contrast to an ailing healthcare system. We aim to review the extent of implementation of mHealth in the management of DM in Africa, and estimate its impact in helping patients achieve desired glycaemic target, sustain control and prevent complications in the past decade.Methods and analysis Studies assessing the utilisation of mhealth in the management of patients with DM in Africa will be considered based on the PICO method: Population, Intervention, Comparator, and Outcomes. Medline, PubMed, SCOPUS and the Pan African Clinical Trials Registry, among others will be searched. Two authors independent of each other shall screen titles and abstracts retrieved using the search strategy, retrieve the full text articles and assess them for eligibility and extract data. A third reviewing author will be brought in to resolve any disagreement between the two authors by discussion. The ‘Cochrane Collaboration Risk of Bias Tool’ will be used to assess the quality of included studies. A narrative synthesis of extracted data and, where the characteristics of the eligible studies permit, a meta-analysis (which will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines) will be done.Ethics and dissemination No ethical approval will be required since only published data will be used. Dissemination of results will be through peer reviewed publication and conference presentation.PROSPERO registration number CRD42021218674.